Smk Pariwisata Di Pekanbaru Dengan Pendekatan Prinsip Desain Le Corbusier - Arifia Azas; Pedia Aldy; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The Tourism Vocational High School with Le Corbusier's Design Principles Approach is a forum that holds formal school activities based on tourism vocational practices to face the professional world, in accordance with Le Corbusier's design principles. Le Corbusier, the originator of modern architectural styles, has a functional and simple view in the application of architectural design. Le Corbusier's architectural style will support the building function of the Vocational Tourism School as a school and implement simplicity. This design aims to be able to support teaching and learning activities of Vocational Tourism that are based on practice. The research methods used include field data collection, literature studies and empirical studies. The results of this study design a building that accommodates Vocational Tourism teaching and learning activities with Le Corbusier's design principle approach in terms of functional forms in accordance with their functions as schools, applying simplicity, and applying other Le Corbusier design principles and creating buildings that are in accordance with the rules precedent architecture of Le Corbusier.Keywords: Le Corbusier, Precedent Architecture, Tourism Vocational High School